INTERPRETASI SPIRITUALITAS PADA KARYA SENI PATUNG AMRIZAL SALAYAN - Didit Endriawan; Donny Trihanondo (ATRAT: Jurnal Seni Rupa, 2015)
The spirituality experienced from one person to another person is vary from person to person. Spirituality has two meaning, the personal spirituality and religious spirituality. The first one is the experience of one's personal spirituality that have an impact on his personal consciousness and/or influence attitudes and behavior, without concerningthe beliefs of that person. While religious experience is spirituality that experience of someone who has a relationship with the religion that he embraced so that these experiences have an impact on his attitudes and behavior.To a certain point artist spiritual experience has a special meaning in his life. The experience can be an inspiration to the artists represented into anartwork. One Indonesian artists whose works are laden with spiritual values are Amrizal Salayan, and AD Pirous. Salayan Amrizal track record as one of the Indonesian artists is without doubt. His works in every exhibition presents many contemplative visual form, for example, his work entitled “Manusia Daun Pisang”, “Ia Ada dengan Ketiadaannya”, and others.With an aesthetic approach to Islam and Art Language, in this study, the discussion focused on the works Amrizal Salayan, AD. Pirous and others to study about spiritual values contained in their works.Keywords: Spirituality, Artworks, Artists in Indonesia, Islamic Aesthetics, Art Language__________________________________________________________________ Pengalaman spiritualitas antara satu orang dengan orang lain tentunya berbeda-beda. Spiritualitas memiliki dua pemahaman yaitu spiritualitas personal dan spiritualitas religius. Spiritualitas personal yaitu pengalaman seseorang yang berdampak pada kesadaran pribadinya sehingga mempengaruhi sikap dan perilakunya, terlepas dari agama apapun terhadap orang tersebut. Sedangkan spiritualitas religius yaitu pengalaman seseorang yang memiliki hubungan dengan agama yang dia anut sehingga pengalaman tersebut berdampak pada sikap dan perilakunya. Bagi seorang seniman tertentu pengalaman spiritual memiliki arti khusus dalam kehidupannya. Pengalaman tersebut mampu menjadi inspirasi sehingga seniman tersebut merepresentasikannya menjadi sebuah karya seni. Salah satu seniman Indonesia yang karya-karyanya sarat dengan nilai-nilai spiritual adalah Amrizal Salayan. Rekam jejak Amrizal Salayan sebagai salah satu seniman Indonesia tidak diragukan lagi. Karya-karyanya dalam setiap pameran banyak menghadirkan wujud visual yang kontemplatif, contohnya karyanya yang berjudul “Manusia Daun Pisang”, “Ia Ada dengan Ketiadaannya”, dan lain-lainnya. Dengan pendekatan estetika Islam dan Bahasa Rupa, pada penelitiannya ini, pembahasannya fokus pada karya-karya Amrizal Salayan untuk dikaji soal nilai-nilai spiritualitas yang terkandung di dalamnya. Kata Kunci: Spiritualitas, Karya Seni Rupa, Seniman Indonesia, Estetika Islam, Bahasa Rupa